2005
DOI: 10.1002/jbm.b.30189
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of poly(L‐lactide‐co‐glycolide) (PLGA) microbubbles as a contrast agent for myocardial contrast echocardiography

Abstract: A kind of absorbable PLGA microbubble-based contrast agent (PLGA microspheres with porous or hollow inner structure) was fabricated by an improved double emulsion-solvent evaporation method. The contrast efficiency was evaluated and proved both in vitro and in vivo. By adjusting the polymer concentration and volume of the inner aqueous phase during the fabrication of microbubbles, the inner structure of the microbubbles could be controlled. Both air-filled and perfluoropropane-filled microbubbles can opacify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 31 publications
0
72
0
1
Order By: Relevance
“…14 Many stabilizers such as polyvinyl alcohol, polyvinyl pyrrolidone, and Tween ® 80 are added to prevent PLGA NP aggregation during PLGA NP preparation. 15,16 These stabilizers significantly limit their biomedical application because they do not have functional groups for further modifications. Synthesizing stabilizer-free and biodegradable PLGA NPs was previously successful when significant amounts of drugs could be encapsulated in PLGA NPs , 100 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…14 Many stabilizers such as polyvinyl alcohol, polyvinyl pyrrolidone, and Tween ® 80 are added to prevent PLGA NP aggregation during PLGA NP preparation. 15,16 These stabilizers significantly limit their biomedical application because they do not have functional groups for further modifications. Synthesizing stabilizer-free and biodegradable PLGA NPs was previously successful when significant amounts of drugs could be encapsulated in PLGA NPs , 100 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have proposed the use of polymers to increase the stability of UCAs, since polymeric shells would resist dissolution and acoustic pressures better than the monomolecular layers of lipids or proteins usually stabilizing commercial UCAs. [7][8][9][10] Moreover, because of their high difference of density with air and their poor solubility in water, perfluorocarbons have been shown to increase both the stability and the echogenicity of UCAs. [11] Lanza et al [12] as well as Wickline et al [13] have shown that nanoemulsions of liquid perfluorocarbons in water have interesting ultrasound properties similar to gaseous perfluorocarbons, particularly at high frequencies (>15 MHz), and they suggest that such agents would be useful for small animal imaging.…”
mentioning
confidence: 99%
“…After further stirring with Ultra-turrax T10 (IKA) for 10 min (works for 1 min and stops for 1 min) over ice water, organic solvents were then evaporated by magnetic stirring for about 3 h at room temperature. [15] Characterization Particle size was measured through dynamic light scattering with a Malvern Zetasizer Nano ZS (Malvern Instruments Ltd., Malvern, Worcestershire, UK). Transmission electron microscopy (TEM) images were recorded on a JEOL-2100F instrument using an accelerating voltage of 200 kV.…”
Section: Synthesis Of Plga-block-pegmentioning
confidence: 99%